Transoral robotic surgery in the management of head and neck squamous cell cancer with unknown primary. (2nd January 2020) - Nilsson, Johan S.; Wahlberg, Peter; Greiff, Lennart
Abstract: Background: Transoral robotic surgery (TORS) assisted base of the tongue (BOT) resection has been suggested as part of the work-up for head and neck squamous cell cancer with unknown primary (HNSCC-CUP). Success rates vary with regard to identification of primary BOT lesions, and cases with likely such lesions appear to be included in previous reports. Objectives: To analyse the possible benefits of a superficial TORS-assisted BOT resection in thoroughly investigated HNSCC-CUP. Material and methods: Retrospectively, 13 patients subjected to superficial TORS-assisted BOT resections due to HNSCC-CUP, where previous thorough work-ups including PET-scans had been performed and primary lesions had still not been identified, were reviewed. Results: Nodal status, according to the TNM-8 classification, was N1, N2, N2a, N2b, N2c, and N3, respectively, for 7, 1, 1, 4, 0, and 0 patients. In 38% of the cases, T1 BOT cancers were identified using superficial TORS-assisted BOT resections and treatments adjusted. Conclusion: Addition of a superficial TORS-assisted BOT resection to the work-up of HNSCC-CUP frequently identifies primary lesions and alters the treatment for this group of patients even after thorough work-up.